2020
DOI: 10.3390/ijerph17041350
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia in Schizophrenia Patients: Prevalence and Quality of Life

Abstract: Sleep disorders are often not regarded as an important health problem, despite their impact on heath. Insomnia is the most frequent sleep disorder in mental health. The aim is to quantify the prevalence of insomnia in a population with schizophrenic disorder and assess its influence on quality of life. This is a descriptive, analytical and cross-sectional study conducted in a sample of 267 schizophrenic patients over 18 years of age using consecutive non-probabilistic sampling. The variables of interest were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 48 publications
(54 reference statements)
5
20
0
Order By: Relevance
“…Notably, this study employed diagnostic assessment, thus stricter criteria, which might suggest that our rates should have been even higher. However, the frequency of our findings is somewhat higher than other studies investigating insomnia symptoms in schizophrenia samples (Hou et al, 2017), yet similar to other (Batalla-Martin et al, 2020) and also similar to studies using stricter insomnia criteria in studies of bipolar disorder samples (Harvey, Schmidt, Scarna, Semler, & Goodwin, 2005;Kanady, Soehnera, & Harvey, 2015;Ng et al, 2015).…”
Section: The Frequency Of Sleep Disturbances In Severe Mental Disorderssupporting
confidence: 89%
“…Notably, this study employed diagnostic assessment, thus stricter criteria, which might suggest that our rates should have been even higher. However, the frequency of our findings is somewhat higher than other studies investigating insomnia symptoms in schizophrenia samples (Hou et al, 2017), yet similar to other (Batalla-Martin et al, 2020) and also similar to studies using stricter insomnia criteria in studies of bipolar disorder samples (Harvey, Schmidt, Scarna, Semler, & Goodwin, 2005;Kanady, Soehnera, & Harvey, 2015;Ng et al, 2015).…”
Section: The Frequency Of Sleep Disturbances In Severe Mental Disorderssupporting
confidence: 89%
“…One study of first episode psychosis patients ( n = 280) found that 22.6% suffered from clinical insomnia, especially prominent in individuals who smoked, used alcohol, and were not on antipsychotic treatment [ 43 ]. A very similar prevalence (23.2%) has been reported among medicated persons with schizophrenia [ 38 ]. Reeve et al [ 44 ], on the other hand, found that the rate of insomnia reached 50% in 60 patients with early psychosis (mostly schizophrenia).…”
Section: Sleep and Psychosissupporting
confidence: 72%
“…Findings from schizophrenia are very relevant to delusional disorders because of the considerable overlap between the two disorders. In schizophrenia, sleep quality has been correlated with the degree of paranoid ideation [ 36 ], with hostility and violence [ 37 ], with poor quality of life [ 38 , 39 ], with memory functions [ 40 ], with physical activity [ 41 ], and with dopamine signaling [ 42 ]. These correlations may well also apply to DD.…”
Section: Sleep and Psychosismentioning
confidence: 99%
“…Among mental disorders, psychosis, characterized by clinical, cognitive, and functional impairment, represents one of the most studied. A vast body of literature has described disrupted sleep (e.g., Batalla-Martín et al, 2020;Ong et al, 2020), aberrant sense of self (e.g., Keromnes et al, 2018;Moe & Docherty, 2014;Parnas & Handest, 2003), and impaired social cognition (Green et al, 2015;Vaskinn & Horan, 2020) as core features of psychosis. These deficits, along with anomalous bodily experiences (Nyboe et al, 2016;Stanghellini et al, 2012), and neuroanatomical and functional abnormalities within the insular cortex (Ebisch et al, 2013;Ebisch et al, 2014;Karrer et al, 2019), provide indirect evidence to suggest that interoception may be impaired in those with psychosis.…”
mentioning
confidence: 99%